Steady-state centrifugal input via the lateral olfactory tract modulates spontaneous activity in the rat main olfactory bulb. (21st April 2017) - Ford, Neil C.; Griff, Edwin R.
Highlights: Topical lidocaine application selectively inhibits tonic action potential conduction in the lateral olfactory tract (LOT). The rate of spontaneous activity of glomerular layer units and mitral cell units was significantly dampened by LOT block. Tonic inhibitory and excitatory drive to the MOB via the LOT dynamically shapes the spontaneous activity of MOB neurons. Abstract: Mitral and tufted cells in the main olfactory bulb (MOB) of anesthetized rats exhibit vigorous spontaneous activity, action potentials produced in the absence of odor stimuli. The central hypothesis of this paper is that tonic activity of centrifugal input to the MOB modulates the spontaneous activity of MOB neurons. The spontaneous activity of centrifugal fibers causes a baseline of steady-state neurotransmitter release, and odor stimulation produces transient changes in the resulting spontaneous activity. This study evaluated the effect of blocking centrifugal axon conduction in the lateral olfactory tract (LOT) by topically applying 2% lidocaine. Mean spontaneous activity of single bulbar neurons was recorded in each MOB layer before and after lidocaine application. While the spontaneous activity of most MOB neurons reversibly decreased after blockade of the LOT, the spontaneous activity of some neurons in the mitral, tufted and granule cell layers increased. The possible mechanisms producing such changes in spontaneous activity are discussed in terms of the tonic, steady-state release of excitatory and/or inhibitory signals from centrifugal inputs to the MOB. The data show for the first time that tonic centrifugal input to the MOB modulates the spontaneous activity of MOB interneurons and projection neurons. The present study is one of the few that focuses on steady-state spontaneous activity. The modulation of spontaneous activity demonstrated in this study implies a behaviorally relevant, state-dependent regulation of the MOB by the CNS.